Superconducting properties of bulk Bi(Pb)-Sr-Ca-Cu-O with nanopowder CoFe2O4 addition - Lau, Kok-Tee; Ayof, Mohd Nizam (UTeM, 2006)
The efforts to improve the superconducting properties of high temperature superconductor in the aspect of supercurrent transport ability have been made by introducing artificial pinning sites. Several techniques include heavy ion bombardment, proton irradiation, neutron irradiation and atomic substitutions had been used and found its own difficulties when applied in large-scale production. One of solution to overcome these problems is the addition of nanometer size particles as pinning centres to the superconductor which had been found effective to improve the pinning strength of superconductor In this paper, the superconducting properties of bulk Bi(Pb)-Sr-Ca-Cu-O with nano-powder CoFe2O4 addition will be investigated by Tc and Jc measurements. Data obtained from XRD and SEM will also be presented.